La poesía en el desarrollo del lenguaje oral en niños de 4 – 5 años. - Gualpa Quinatoa, Katherin Silvana (2022)
This research proposal, it was analyzed the poetry great importance in the 4 to 5 years old children lexical progress which it is performed ha research work analysis "Linguistic awareness and the oral language development in the 4 to 5 years old childrent" to get a problem prior diagnosis that resents into "Pujilí" Educational Unit, based on, which have been proposed activities, what help solve the vocalization and inadequate pronunciation problem, what have infants have. It had been taken as an approach the constructivist pedagogical model, since it helps the children active participation to interact in the classes development to build, create, reflect about their knowledge and their own learning. That is, why, the main resource, what has been proposed for the language development, through poems has been the creation “Pictographic Poems Book", therefore, the book consists fourteen well-known poems rescued from Pujilí canton, and to complement the poetic recitation, it has been created a giant puppet to help with body expression, when reciting poetry. Finally, this research proposal has been assessed and validated by the experts, since the criticisms towards the didactic start the pre-reading and later, pre-writing, through recreational activities and playful resources.